Islamic Economic Perspectives in Buying in the Traditional Market Tuesday Panam Tampan Kota Pekanbaru - Nurhadi (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2019)
This study aims to determine the review of Islamic economics related to business ethics in buying and selling transactions in the traditional market of Selam Panam, Tampan District, Pekanbaru City. The subject of research for traders, the object of business behavior. Data collection techniques with observation, interviews and documentation. Analysis of the data is descriptive analysis where the data obtained is analyzed and presented in the form of an analysis table. Based on the results of observations and questionnaires obtained from traders, there are several points of business ethics that are applied, namely halal, trustworthiness, justice, non-coercionand endorsement, so this is in line with business ethics in buying and selling transactions according to the Sharia Economy. However, at honest and usury points there are still fraudulent actions that are not appropriate. So it can be concluded that business ethics in buying and selling transactions in the traditional markets Tuesday Panam Tampan Pekanbaru which are reviewed according to the Sharia Economy in general have not been well implemented by traders. Traders still commit fraud (reducing doses, hiding defects of goods, and others), this is contrary to Islamic law.